EVALUATION OF ELECTRIC CONDUCTIVITY AND MILK LACTOSE AS A PRE-INDICATOR OF MASTITIS IN THARPARKAR DAIRY CATTLE - Sharma, Amit; Sharma, Sanjita; Singh, Navan; Poonia, Mahendra Pal (Indian Journal of Animal Production and Management, 2017)
Somatic cell count (SCC) in milk has been shown to be an excellent marker for subclinical mastitis but verydifficult to execute at farm level. Due to the damage to the udder tissue, concentrations of lactose decreaseand concentrations of Na+ and Cl increases in milk which results in increase in electric conductivity. Thepresent investigation was carried out to investigate the correlation of milk lactose and electric conductivitywith somatic cell count and can be used as an indicator to detect subclinical mastitis (SCM) in Indigenouszebu Tharparkar cattle. Total 466 milk samples were screened for somatic cell count, 198 samples werepositive for subclinical mastitis. All the samples were analyzed for electrical conductivity (EC) and milklactose by deluxe electric conductivity meter manufactured by Systronics India limited, Ahamdabad andultrasonic milk analyzer manufactured by Rajasthan Electronics & Instrument Limited (REIL), Jaipurrespectively. The result demonstrated statistically significant (p